(untitled) - Hejhalova, Bozena (Doprava a spoje, 2009)
Transition of field of activities from the side of the state to the autonomy in the area of regional public passenger transport, comparison of tax incomes in the individual autonomous regions and expenditures related to transport, especially with assurance of transport services, comparison of selected indicators in the suburban road transport according to the regions.